2011
DOI: 10.4049/jimmunol.1100578
|View full text |Cite
|
Sign up to set email alerts
|

Nod1 Activation by Bacterial iE-DAP Induces Maternal–Fetal Inflammation and Preterm Labor

Abstract: There is a strong association between infection and prematurity; however, the underlying mechanisms remain largely unknown. Nod1 and Nod2 are intracellular pattern recognition receptors that are activated by bacterial peptides and mediate innate immunity. We previously demonstrated that human first-trimester trophoblasts express Nod1 and Nod2, which trigger inflammation upon stimulation. This study sought to determine the expression and function of Nod1 and Nod2 in third-trimester trophoblasts, and to characte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
43
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 68 publications
(50 citation statements)
references
References 56 publications
5
43
2
Order By: Relevance
“…A recent study demonstrated that administration of iE-DAP to pregnant mice caused preterm birth, reduced fetal weight, and induced proinflammatory responses at the maternal-fetal interface (21), which was in part consistent with our study. We found new evidence that among the various fetal tissues, including the placenta and yolk sac, the production of CCL2 and IL-6 after the stimulation with FK565 was observed predominantly in the vascular tissue, wherein Nod1 was expressed at high levels in a physiological condition.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…A recent study demonstrated that administration of iE-DAP to pregnant mice caused preterm birth, reduced fetal weight, and induced proinflammatory responses at the maternal-fetal interface (21), which was in part consistent with our study. We found new evidence that among the various fetal tissues, including the placenta and yolk sac, the production of CCL2 and IL-6 after the stimulation with FK565 was observed predominantly in the vascular tissue, wherein Nod1 was expressed at high levels in a physiological condition.…”
Section: Discussionsupporting
confidence: 82%
“…Other groups also reported that stimulation of Nod1 directly activated blood vessels and induced the inflammatory response via activation of NF-kB and MAPK pathways, which eventually caused experimental shock in vivo (26,27). However, there was no evidence of cellular infiltration in the arteries of the placentae or fetuses in the current study, which is similar to a previous study using another Nod1 ligand (iE-DAP) (21). When a higher dose of FK565 was injected into pregnant mice, vascular inflammation was induced only in the pregnant mice, but not in the fetal and maternal vessels of the placentae or fetuses (Supplemental Fig.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…The NOD1 ligand, iEDAP, can induce preterm delivery in a murine model. When lower doses that did not induce preterm delivery were used there was heightened inflammation at the materno-fetal interface and in the fetus itself (Cardenas, Mulla et al 2011). Immunohistochemical studies have shown that the CLR DC-SIGN is expressed by fetal macrophages (Hofbauer cells) within the chorionic villi of the term placenta (Geijtenbeek, van Vliet et al 2001).…”
Section: Placentamentioning
confidence: 99%
“…In contrast only NOD1 is expressed in term trophoblast cells. This corresponds to the functional outputs of first versus third trimester trophoblast cells; first trimester cells respond to both MDP and iE-DAP, and third trimester cells only respond to iE-DAP (Abrahams 2011;Cardenas, Mulla et al 2011). The NOD1 ligand, iEDAP, can induce preterm delivery in a murine model.…”
Section: Placentamentioning
confidence: 99%